اجراءات و مراحل عقد بيع السلم في البنوك الاسلامية دراسة حالة بنك البركه - مصباح, مصباحي; آيه, معامير; نريمان, مصباحي (جامعة الوادي - University of Eloued, 2023)
"يهدف هذا البحث إلى التعريف و إبراز أهم مراحل و إجراءات عقد بيع السلم في المصارف الإسلامية، وذلك بأخذ عينة من المصرف الإسلامي بنك البركة الجزائري وكالة ي ولاية الوادي، ومن أجل بلوغ هذا الهدف تم الاعتماد على المنهج الوصفي في الفصل النظري، حيث تطرقنا نظريا للمصارف الإسلامية و عقد بيع السلم و كذلك تم الاعتماد المنهج التحليلي وقد أستعمل في تحليل اختلاف الفقهاء و تحليل مواد عقد بيع السلم ، في البنوك الإسلامية. تم التوصل إلى أن عقد السلم يعتبر من أهم الصيغ التمويلية في المصارف الإسلامية و من ضمن الأكثر استخداما من بين الصيغ الأخرى ،حيث تم التطرق لكل مواده و مراحل تطبيقه اعتمادا على دراسة ميدانية داخل الوكالة محل الدراسة ." "Abstract :This research aims to define and highlight the most important stages and procedures of the contract for the sale of peace in Islamic banks, by taking a sample from the Islamic Bank of Al Baraka Algerian Agency in the state of the valley, and in order to achieve this goal was based on the descriptive approach in the theoretical chapter, where we dealt theoretically for Islamic banks and the contract of sale of peace as well as the adoption of the analytical approach has been used in the analysis of the difference of jurists and analysis of the materials of the contract of sale of peace, in Islamic banks . It was concluded that the Salam contract is one of the most important financing formulas in Islamic banks and among the most used among other formulas, where all its articles and stages of application were addressed depending on a field study within the agency under study ."
Keywords: المصارف الإسلامية، بنك البركة الجزائري، عقد بيع السلم.; Islamic banks, Algerian Al Baraka Bank, Salam sale contract.